Heart Rate Variability in Patients with Acute Ischemic Stroke at Different Stages of Renal Dysfunction: A Cross-sectional Observational Study - Lin Wei; Wen-Bo Zhao; Huan-Wen Ye; Yan-Hua Chen; Xiao-Pei Zhang; Yan Huang; Ye-Feng Cai; Quan-Fu Chen; Su-Yue Pan (Chinese Medical Journal, 2017)
Background: Renal function is associated with mortality and functional disabilities in stroke patients, and impaired autonomic function is common in stroke, but little is known regarding its effects on stroke patients with renal dysfunction. This study sought to evaluate the association between autonomic function and stroke in patients with renal dysfunction. Methods: This study comprised 232 patients with acute ischemic stroke consecutively enrolled from February 2013 to November 2014 at Guangdong Provincial Hospital of Chinese Medicine in China. All patients recruited underwent laboratory evaluation and 24 h Holter electrocardiography (ECG). Autonomic function was measured based on the heart rate variability (HRV) using 24 h Holter ECG. Renal damage was assessed through the estimated glomerular filtration rate (eGFR), and stroke severity was rated according to the National Institutes of Health Stroke Scale (NIHSS). The Barthel index and modified Rankin score were also determined following admission. All the clinical covariates that could potentially affect autonomic outcome variables were adjusted with linear regression. Results: In the patients with a mild or moderate decreased eGFR, the values for the standard deviation of the averaged normal-to-normal RR interval (SDANN) index (P = 0.022), very low frequency (VLF) (P = 0.043), low frequency (LF) (P = 0.023), and ratio of low-to-high frequency power (LF/HF) (P = 0.001) were significantly lower than those in the patients with a normal eGFR. A multinomial linear regression indicated that eGFR (t = 2.47, P = 0.014), gender (t = −3.60, P < 0.001), and a history of hypertension (t = −2.65, P = 0.008) were the risk factors of LF/HF; the NIHSS score (SDANN index: t = −3.83, P < 0.001; VLF: t = −3.07, P = 0.002; LF: t = −2.79, P = 0.006) and a history of diabetes (SDANN index: t = −3.58, P < 0.001; VLF: t = −2.54, P = 0.012; LF: t = −2.87, P = 0.004) were independent factors for the SDANN index, VLF, and LF; the Oxfordshire Community Stroke Project (t = −2.38, P = 0.018) was related to the SDANN index. Conclusions: Autonomic dysfunction is aggravated with the progression of eGFR stage in patients with acute ischemic stroke; the eGFR is an independent factor of LF/HF in the adjusted models. Stroke severity and a history of diabetes are more significantly associated with HRV in patients with acute ischemic stroke at different stages of renal dysfunction.